In vitro activity test is a critical evaluation to screen the potential biocontrol agent. We developed a selective medium for quantitative in vitro activity evaluation of bacterial biocontrol agents against pathogenic Vibrio in aquaculture. Sensitivity test of bacterial biocontrol and Vibrio spp. to nine antibiotics showed that oxytetracycline inhibited the growth of Vibrio spp., but did not inhibit the growth of the bacterial biocontrol. This selective inhibition activity of oxytetracycline sug - ALIM ISNANSETYO; . MUHTADI; INDAH ISTIQOMAH; KAMISO HANDOYO NITIMULYO; . TRIYANTO (Bogor Agricultural University, Indonesia, 2011)
In vitro activity test is a critical evaluation to screen the potential biocontrol agent. We developed a selective medium for quantitative in vitro activity evaluation of bacterial biocontrol agents against pathogenic Vibrio in aquaculture. Sensitivity test of bacterial biocontrol and Vibrio spp. to nine antibiotics showed that oxytetracycline inhibited the growth of Vibrio spp., but did not inhibit the growth of the bacterial biocontrol. This selective inhibition activity of oxytetracycline suggested this antibiotic might be supplemented to establish a selective medium. The MIC of oxytetracycline against V. harveyi, V. parahaemolyticus, and V. algosus were 120, 250, and 120 mg/ml, respectively. These concentration did not inhibit the growth of bacterial biocontrols. Therefore, oxytetracycline was supplemented at 250 µg/ml in Zobell agar medium. This medium was used as a selective medium to enumerate the density of bacterial biocontrol. In vitro activity test of bacterial biocontrol (RLP1) against V. parahaemolyticus showed that strain RLP1 at density of 104 and 106 cells/ml was able to kill V. parahaemolyticus during 6 h incubation. At lower density, 102 cells/ml, this bacterial biocontrol agent was able to kill the pathogenic Vibrio during 12 h incubation. This study discovered a selective medium for the bacterial biocontrol and Vibrio spp. and provided the results of its application in the evaluation of in vitro activity of a bacterial biocontrol agent against V. parahaemolyticus. The results also revealed that strain RLP1 is a potential bacterial biocontrol against vibriosis in marine aquaculture.